Assessing influences of public open space on well being of low-cost housing residents in Malaysia post COVID-19 - Mohmmad Zin, Harith (2023)
Malaysian Well-being Index (MyWI) 2020 reported that the well-being of low-cost housing residents was inimical due to the loss of opportunities for recreation because of movement control order (MCO) during the COVID-19 pandemic. Residents were restricted from moving, including visiting public open space (POS), which affected them physically and mentally because of the poor condition of their living space, such as overcrowding and poor ventilation. Therefore, this study aims to assess the importance of adaptable POS on physical and mental well-being from the perspective of low-cost housing residents during and post pandemic. This study employed a qualitative research method using three case studies at Projek Perumahan Rakyat (PPR) in Lembah Pantai, Kuala Lumpur representing low-cost housing development. Semistructured interviews and field observations are the primary methods for data collection. In total, 15 POS users were purposively selected for the interviews and observations were conducted at different times and days. Findings were analysed using ATLAS.ti v22 software and content analysis. The results show that the pandemic negatively affected low-cost housing residents' physical and mental well-being because of the limited space for recreation and social activities. The residents needs POS and appreciate it more than before. Therefore, POS in low-cost housing needs physical and social improvement by implementing design principles that are adaptable to shocks and stresses for a good well-being of residents.